2016
DOI: 10.1007/s00441-016-2357-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in keratins and alpha-smooth muscle actin during three-dimensional reconstitution of eccrine sweat glands

Abstract: We have examined the changes of keratins and alpha-SMA at various time points in order to investigate the development and differentiation of eccrine sweat gland cells during the course of three-dimensional (3D) reconstitution. Mixtures of eccrine sweat gland cells and Matrigel were injected subcutaneously into the inguinal regions of nude mice. At 1, 2, 4, 6, 8, 14, 21, 28, 35, and 42 days post-implantation, Matrigel plugs were removed and immunostained. We found that during 3D reconstitution, keratin and alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…This suggested a certain self-organization potential of isolated eSG cells with some degree of cell-cell communication and interaction in those scaffold-free 3D HD models. Self-organization and -differentiation of coil and duct cells in in vitro models were also reported by other research groups using Matrigel-assisted eSG replicas and their implantation into nude mice [69,70].…”
Section: Characterization Of Sv40t-transduced Eccrine Sweat Gland Duc...supporting
confidence: 71%
“…This suggested a certain self-organization potential of isolated eSG cells with some degree of cell-cell communication and interaction in those scaffold-free 3D HD models. Self-organization and -differentiation of coil and duct cells in in vitro models were also reported by other research groups using Matrigel-assisted eSG replicas and their implantation into nude mice [69,70].…”
Section: Characterization Of Sv40t-transduced Eccrine Sweat Gland Duc...supporting
confidence: 71%
“…Second, the epithelial apical-basal polarity within the 3D model was shown by histochemical analysis with specific SG cell marker proteins like AQP5, CHRM3, CEACAM5, and ANO1. Li et al demonstrated a comparable reconstruction of sweat gland-like structures with Matrigel-cultivated primary cells, which only formed tubular-like structures after transplantation in mice [ 36 , 43 ]. However, the transplantation step makes their model more complicated as compared to our hanging-drop culture and would not be suitable for applications, which prohibit the use of animal models such as screening for cosmetic bioactives.…”
Section: Discussionmentioning
confidence: 99%
“…The decapitation products were positive for K5, Brst-2 and CEA, the commonly used markers for both apocrine and eccrine glands. 14,15 It was worth noting that no obvious inflammatory reaction was observed, which demonstrated that the interaction between apocrine gland secretions and bacteria did not occur in the body.…”
Section: Discussionmentioning
confidence: 98%